Cells and Microbes - Spilsbury, Louise (Oxford University Press, 2010)
The World of Science and Technology The Natural World The World of Arts and Social Studies Also available for each reader: Activity Book Audio CD Pack (Reader and Audio CD) Teacher's Notes and CLIL guidance at www.oup.com/elt/readanddiscover The Activity Book includes 16 pages of chapter-linked activities followed by after-reading whole book activities and a book review; focus on content, vocabulary, and grammar.